2022
DOI: 10.21037/qims-21-308
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of in vivo lumbar spine intervertebral discs using a 3D adiabatic T1ρ prepared ultrashort echo time (UTE-Adiab-T1ρ) pulse sequence

Abstract: Background: T 1ρ has been extensively reported as a sensitive biomarker of biochemical changes in the nucleus pulposus (NP) and annulus fibrosis of intervertebral discs (IVDs). However, no T 1ρ study of cartilaginous endplates (CEPs) has yet been reported because the relatively long echo times (TEs) of conventional clinical T 1ρ sequences cannot effectively capture the fast-decaying magnetic resonance signals of CEPs, which have very short T 2 /T 2 *s. This can be overcome by using ultrashort echo time (UTE) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The NP regions of degenerated discs in the DIR-UTE, IR-FS-UTE, and T 1w -FS-UTE images show relatively higher signals than those in normal discs. This may be because of shortened T 1 relaxation time in the NP due to disc dehydration [ 8 , 30 , 31 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The NP regions of degenerated discs in the DIR-UTE, IR-FS-UTE, and T 1w -FS-UTE images show relatively higher signals than those in normal discs. This may be because of shortened T 1 relaxation time in the NP due to disc dehydration [ 8 , 30 , 31 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown T2 mapping values correlate with the Pfirrmann classification, which can be used as an imaging biomarker for quantitative evaluation of the IVD, allowing for the better assessment of its function ( 35 ). Compared with T2 relaxation time measurement, T1ρ has a wider dynamic range to evaluate IDD, which may be sensitive to early degenerative changes, such as those in PG content in the IVD ( 36 , 37 ). In recent years, the number of studies on the application of DTI to IDD have gradually increased ( 38 - 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5a shows the IR-FS-UTE contrast mechanism to highlight short-T2 signal with efficient suppression of long-T2 water and fat. [25][26][27] The IR-FS-UTE sequence uses a long adiabatic inversion pulse to invert the longitudinal magnetizations of long-T2 tissues such as the nucleus pulposus (NP) in the vertebral disk. A chemical shift-based fat saturation module is used to further suppress fat signal.…”
Section: Adiabatic Inversion Recovery Fat-saturated Utementioning
confidence: 99%
“…Of the various morphological imaging techniques, adiabatic IRbased approaches, including single IR-UTE, [15][16][17][18][19][20] dual-IR-UTE, [21][22][23] double-IR-UTE, 24 IR-FS-UTE, [25][26][27] and STAIR-UTE, [28][29][30] appear to provide more uniform suppression of long-T2 water and fat signals. This is attributable to the insensitivity of adiabatic pulses to B1 and B0 inhomogeneities.…”
Section: Part Iii: Challenges and Future Workmentioning
confidence: 99%